2021
DOI: 10.5603/fm.a2020.0140
|View full text |Cite
|
Sign up to set email alerts
|

Parietal foramen: incidence and topography

Abstract: The parietal foramen (PF) is a small inconsistent aperture located at the border of the middle 1 /3 and posterior 1 /3 of the parietal bone near the sagittal suture and is considered an emissary foramen. Cranial emissary foramina are of utmost importance due to the structures that traverse the foramen. Variations in these foramina are common. Knowledge of the PF is important when performing neurosurgical procedures as the emissary vessels are at risk. The present study used 100 dry adult calvaria to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
3
5
2
Order By: Relevance
“…Depending on whether the third fontanel shuts, the PF might be unilateral or bilateral (Yılmaz et al, 2014;Agarwal et al, 2015) . This statement is consistent with the increased prevalence found in this current study, which found a 35.1 % existence of bilateral PF, that is higher than those of Naidoo et al (2021) 32 % andDebbarma et al (2015) (30 %) (Debbarma et al, 2015;Naidoo et al, 2021) . But, this discovery is less than those of Murlimanju et al (2015) (55.2 %) and Gangmei et al (2018) (62.5 %).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Depending on whether the third fontanel shuts, the PF might be unilateral or bilateral (Yılmaz et al, 2014;Agarwal et al, 2015) . This statement is consistent with the increased prevalence found in this current study, which found a 35.1 % existence of bilateral PF, that is higher than those of Naidoo et al (2021) 32 % andDebbarma et al (2015) (30 %) (Debbarma et al, 2015;Naidoo et al, 2021) . But, this discovery is less than those of Murlimanju et al (2015) (55.2 %) and Gangmei et al (2018) (62.5 %).…”
Section: Resultssupporting
confidence: 93%
“…According to this study, mean incidence of unilateral PF is 43.3 % of cases (right: 23 %, left: 20.3 %), this finding is higher than the findings of Naidoo et al (2021) (35 %) and Berge & Bergman (2001) (30 %). The recognition of emissary foramina, like the PF, is critical for clarification of regional vasculature and differentiating these foramina from variation anatomy (Shantharam & Manjunath, 2018).…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…CBO has been given other designations, such as enlarged parietal foramina (if more than 5 mm in diameter), foramina parietalia permagna, fenestrae parietals symmetricae, or Catlin mark (due to the high incidence of this bone defect in the Catlin family, as described by Goldsmith, who observed this malformation in 16 members across five generations [ 1 - 4 , 11 , 12 ]. Its etiology has been attributed to an abnormality in intramembranous ossification during the fifth month of gestation, and several gene mutations have been described that make this condition hereditary in nature, such as loss of function mutations in human homeobox genes MSX2 in chromosome 5 and ALX4 in chromosome 11 [ 3 , 5 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It had a mean diameter of 1.55 mm and was located at a mean distance of 9.02 mm lateral to the sagittal suture. 7 Enlarged parietal foramina may be identified in addition to the ordinarily sized and positioned parietal emissary foramina. 8 In South Indian skulls, the parietal emissary foramen was present at the junction of middle and posterior thirds of the parietal bone in 71.5% of skulls, at a mean distance of 6.7 mm (right) and 6.8 mm (left} lateral to the sagittal suture: solitary in 62.9%, double in 6.9%, triple in 1.7%, unilaterally absent in 32.7%, and bilaterally absent in 12.1% of skulls.…”
Section: Parietal Emissary Foramenmentioning
confidence: 99%